The physics of Christianity - Tipler, Frank J. (Doubleday, 2007)
A respected physicist demonstrates that the essential beliefs of Christianity are wholly consistent with the laws of physics. Tipler takes an new approach to the dispute about the relationship between science and religion. In reviewing centuries of writings and discussions, he realized that there was no serious scientific research into central Christian claims and beliefs, so he embarked on just such an inquiry. Tipler begins by outlining the basic concepts of physics for the lay reader and brings to light the underlying connections between physics and theology. He illustrates how God is completely consistent with the Cosmological Singularity, an entity whose existence is required by physical law. His discussion of miracles provides a credible scientific foundation for many of Christianity's most astonishing claims, including the Virgin Birth, the Resurrection, and the Incarnation.--From publisher description